HUBUNGAN KONDISI KESEHATAN PSIKOSOSIAL LANSIA DENGAN TINGKAT KEMANDIRIAN LANSIA DALAM AKTIVITAS SEHARI-HARI DI RUMAH - Safitri, Maya; Zulfitri, Reni; Utami, Sri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
The last stage of the human life is old age signed with some physical and psychosocial changes. One resultof these changes is decreasing the ability in daily activities. This study aims to determine the correlationbetween psychosocial health conditions with the level of independence in daily activities the elderly in thework area Puskesmas Lima Puluh with descriptive research design correlation with cross sectionalapproach. The sample of the study was 96 people taken based on the inclusion criteria by usingproportionate random sampling technique. The result of research shows that the majority of researchsubjects aged 60-74 years are 87.5%, female sex is 82.3%, marital status of widows is 50.0%, the majorityof elderly do not work as much as 51,0%, majority of elderly have history of disease hypertension by27.1%. Of the 69,8% of respondents had a healthy psychosocial status with self-level category of 53,8%.The result of chi-square test shows p value (0.003) < α (0,05). So it can be concluded that there is acorrelation between psychosocial health conditions with the level of independence in the daily activities ofthe elderly. Psychosocial healthy elderly can be seen from their ability in daily activities independently.Keywords: activity daily living, elderly, psychosocial